Identification of a novel Drosophila opsin reveals specific patterning of the R7 and R8 photoreceptor cells. - Chou, W.H.; Hall, K.J.; Wilson, D.B.; Wideman, C.L.; Townson, S.M.; Chadwell, L.V.; Britt, S.G. (Neuron, 1996)
The function of the compound eye is dependent upon a developmental program that specifies different cell fates and directs the expression of spectrally distinct opsins in different photoreceptor cells. Rh5 is a novel Drosophila opsin gene that encodes a biologically active visual pigment that is expressed in a subset of R8 photoreceptor cells. Rh5 expression in the R8 cell of an individual ommatidium is strictly coordinated with the expression of Rh3, in the overlying R7 cell. In sevenless mutant files, which lack R7 photoreceptor cells, the expression of the Rh5 protein in R8 cells is disrupted, providing evidence for a specific developmental signal between the R7 and R8 cells that is responsible for the paired expression of opsin genes.